Pembrolizumab Induced Ocular Hypotony With Near Complete Vision Loss, Interstitial Pulmonary Fibrosis and Arthritis - Nguyen, Mike; Islam, Md Rafiqul; Lim, Shueh Wen; Sahu, Arvind; Tamjid, Babak (Frontiers in Oncology, 2019)
Clinical outcomes for patients with advanced melanoma have improved significantly with the introduction of immune checkpoint inhibitors. These agents have distinct adverse effects with the potential for heightened host immune responses manifesting as an autoimmune reaction in any organ. We report a unique case who developed pembrolizumab induced arthritis, ocular hypotony with vision loss and pulmonary interstitial fibrosis. A 57-year old gentleman with advanced melanoma was treated with pembrolizumab and attained complete response with no evidence of disease on functional imaging. Treatment was well tolerated with the only side effect being arthritis controlled with low dose steroids. Following a work related blunt trauma to the right eye, the patient developed bilateral visual impairment secondary to ocular hypotony. The ocular hypotony failed to respond to high-dose glucocorticoid and multiple surgeries, and ciliary body atrophy was found intraoperatively. Pembrolizumab was ceased and he remained in complete remission from melanoma. After a further ten months, the patient developed symptomatic pulmonary fibrosis. There was moderate symptomatic improvement with nintedanib, an antifibrotic agent. This case describes two rare and unique adverse effects. Ocular adverse effects occur less than 1% of patients and this is the first case to report immune checkpoint inhibitor related ocular hypotony without uveitis. The incidence of severe pneumonitis is reported to be 2.7% however limited data is available regarding pulmonary interstitial fibrosis. The occurrence of multiple adverse effects in this case including one occurring several months after cessation of treatment highlights the need for vigilance by clinicians who manage patients treated with immune checkpoint inhibitors. Further research is necessary with regards to rare adverse effects of immune checkpoint inhibitors and the relation of these to treatment administration.